1996
DOI: 10.1111/j.1545-5300.1996.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Translatability of Family Concepts into the Japanese Culture: Using the Family Environment Scale

Abstract: Family concepts and their measurements interest many family researchers. There is a question about the extent to which family concepts are universal or influenced by the culture in which the instrument originated. Using the Family Environment Scale (FES), the authors examine the translatability of family concepts into the Japanese culture. Forward- and back-translation processes and cross-cultural assessment of reliability and validity are discussed. We suggest that there may be different degrees of translatab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Intercorrelations among the 10 subscales support the discriminate validity among the scale (Moos & Moos). This measure has been used in a wide range of clinical applications and within various communities (Moos & Moos;Saito et al 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Intercorrelations among the 10 subscales support the discriminate validity among the scale (Moos & Moos). This measure has been used in a wide range of clinical applications and within various communities (Moos & Moos;Saito et al 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Studies carried out in other countries had already confi rmed that the FES is an effective instrument for detecting differences between functional families and families with problems related to the family environment. 4,20,21 Some authors have adopted the term "clinical families" to refer to those that look for psychological or psychiatric treatment for some kind of disorder in the family system. 1,22 Many studies have emphasized the importance of systematized investigations into the family environment that might serve as a basis for better defi ning what a functional family is, and which factors infl uence this evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…17 The discriminant validity and construct validity were evaluated in many studies, and these showed its good capacity to discriminate between families with a functional family environment and those with problems. 4,20,21 The FES can also be used to evaluate the outcomes of interventions; to evaluate the level of adaptation of children and adults to the family environment; and to discriminate within the family environment between groups that differ regarding age, ethnic group and mental health. 2,10,13,19 In other countries, the FES has been used in several recent studies to evaluate the infl uence of the family environment on the psychological characteristics of adolescent children and on psychiatric disorders, including bipolar disorder and alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…Malhotra (1997) has explored the age of marriage in relation to gender in Javanese couples, and Chun and MacDermid (1997) have produced a study on perceptions of family differentiation and individuation among Korean adolescents. Work is being carried out on the applicability of family therapy constructs to Japanese families (Saito et al, 1996) and to Chinese couples (Lewinsohn and Werner, 1997). It has been found that the direct 'translatability' of these constructs is problematic.…”
Section: The First Author Recountsmentioning
confidence: 99%